Conform to the norm. Peer information and sustainable investments - Max Grossmann; Andreas Hackethal; Marten Laudi; Thomas Pauls (Leibniz Institute for Financial Research SAFE, 2023)
We conduct a field experiment with clients of a German universal bank to explore the impact of peer information on sustainable retail investments. Our results show that information about peers' inclination towards sustainable investing raises the amount allocated to stock funds labeled sustainable, when communicated during a buying decision. This effect is primarily driven by participants initially underestimating peers' propensity to invest sustainably. Further, treated individuals indicate an increased interest in additional information on sustainable investments, primarily on risk and return expectations. However, when analyzing account-level portfolio holding data over time, we detect no spillover effects of peer information on later sustainable investment decisions.
Keywords: D14; G11; C93; 330; Household Finance; Sustainable Finance; Experimental Finance; Financial Advice